Emergency health evaluation of affected population during disasters: Are there new approaches? - Seyed Ahmad Bathaei; Hasan Abolghasem-Gorji; Bahram Delgoshaei; Hamid Reza Khankeh (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Disasters are inescapable phenomena. Once they occur, reliable and objective information becomes vital in sound decision-making to respond. Emergency health evaluation of affected population can be used to gather information about the patterns of access to medical care, basic household needs, and other health needs. The objective of this review was to summarize evidence from scientific studies on the various methods of emergency health evaluation following disasters. MATERIALS AND METHODS: A comprehensive list of studies was provided in May 2017 by an extensive search using PubMed, Web of Sciences, Ovid Medline, ProQuest Research Library, and World Health Organization Library. RESULTS: Of the 1592 retrieved articles, 21 articles were included in this review. In a majority of the studies (n = 18), a questionnaire was used and an interview was conducted to collect information, but in three studies, smartphone-based methods were used. Sampling method in most of the studies was cluster sampling in Community Assessment for Public Health Emergency Response method. But in eight studies, random sampling method was used. In a majority of the studies, the demographic status of samples and in 18 studies, the condition of diseases, water, shelters, health, food, mortality rate, and existing medical services were investigated. CONCLUSIONS: Although new methods such as social media and smartphones were already investigated in some articles, but these approaches require further investigation since there is a growing need for new methods.